2010
DOI: 10.3164/jcbn.09-91
|View full text |Cite
|
Sign up to set email alerts
|

Hypotaurine is an Energy-Saving Hepatoprotective Compound against Ischemia-Reperfusion Injury of the Rat Liver

Abstract: Metabolome analyses assisted by capillary electrophoresis-mass spectrometry (CE-MS) have allowed us to systematically grasp changes in small molecular metabolites under disease conditions. We applied CE-MS to mine out biomarkers in hepatic ischemia-reperfusion. Rat livers were exposed to ischemia by clamping of the portal inlet followed by reperfusion. Metabolomic profiling revealed that l contents of taurine in liver and plasma were significantly increased. Of interest is an elevation of hypotaurine, collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 19 publications
4
30
0
Order By: Relevance
“…Of importance were semiquantitative values of [ATP] app in the tumor-bearing liver (Fig. 3f), in the range of approximately 1–2 μmol g −1 liver, levels reasonably comparable with previous observations that determined absolute ATP contents under the snap-frozen procedures [20, 21]. Because intracellular levels of ATP are in the mmol L −1 range, current procedures for data calibration seemed to reproduce reliable intracellular concentrations of metabolites with a rapid turnover.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Of importance were semiquantitative values of [ATP] app in the tumor-bearing liver (Fig. 3f), in the range of approximately 1–2 μmol g −1 liver, levels reasonably comparable with previous observations that determined absolute ATP contents under the snap-frozen procedures [20, 21]. Because intracellular levels of ATP are in the mmol L −1 range, current procedures for data calibration seemed to reproduce reliable intracellular concentrations of metabolites with a rapid turnover.…”
Section: Resultssupporting
confidence: 88%
“…As reported previously [2022], CE–MS enabled us to quantitatively determine more than 2,000 different metabolites at once in small amounts of a single liver sample. Small amounts of the frozen tissue were collected from thick section that was adjacent to the section for IMS.…”
Section: Methodsmentioning
confidence: 64%
“…2). Because these levels were comparable to previous observations that determined the absolute ATP contents after snap‐freezing , the samples obtained in this study were considered to be of sufficient quality.…”
Section: Resultssupporting
confidence: 82%
“…In this study, increased urinary levels of taurine and hypotaurine were observed in EHBR. Also, recent metabolomic studies have demonstrated that these metabolites are increased under several conditions such as hepatic ischemia/reperfusion injury and after partial hepatectomy in rats, suggesting the important role played by these metabolites in the repair process after cellular damage. In EHBR, reduced biliary excretion may increase their systemic exposure to harmful compounds including some bile acids and other endogenous materials.…”
Section: Resultsmentioning
confidence: 99%